Earth for social housing in Palestine: an alternative for a sustainable refurbishment of building’s envelopes - Alatawneh, Bader (Journal of Materials and Environmental Scienc, 2016)
The suitable climates in the cities of Jericho and Gaza boosted the emergence of new attempts to revive earthen architecture on organizational and individual levels. These attempts produced a number of earthen buildings in the last few years following the crucial need to find alternative low cost material instead of natural stone, which is used in a large scale in Palestine. Similar attempts had a certain response to the social needs and economic situation there. This paper focuses on the possibility of using earth as an alternative material to refurbish the envelopes of existing housing units including two categories; firstly, refurbishing envelopes of housing units those were partially destroyed during attacks (ex. in Gaza, about 27% of the housing units were damaged in 2014). Secondly, refurbishing existing houses envelopes to follow the basic environmental considerations. Both categories respect the sustainability dimensions; the social contexts, economic levels of occupants, beside the attention toward the technical and environmental improvements of earth in the future. Keywords: Earthen envelopes, refurbishment, sustainability, building materials, social and economic aspects. Mots clés: enveloppes de terre, rénovation, matériaux de construction, aspects sociaux et économiques
Keywords: Earth Architecture, Earthen Buildings, Sustainability, sustainable building, sustainable architecture; sustainable refurbishment, social housing, building envelope